Investment of human resources in internal control systems and designation as the most admired firms: A corporate governance perspective - Kim, Suyon (Edelweiss Applied Science and Technology, 2025)
The purpose of this study is to examine the impact of investments in human resources for internal control systems on the likelihood of being selected as one of Korea’s most admired companies, with a specific focus on the moderating role of corporate governance. Using data from non-financial firms listed on the Korean stock exchange between 2016 and 2021, the analysis reveals that both quantitative and qualitative aspects of human resource investment in internal control systems significantly enhance corporate reputation. Specifically, the number of employees dedicated to internal control functions and the inclusion of certified public accountants positively influence corporate reputation. Corporate governance is analyzed as a moderating factor. Results indicate that robust human resource investments in internal control systems significantly enhance corporate reputation. Furthermore, strong corporate governance amplifies this effect by fostering transparency, accountability, and stakeholder trust. The findings underscore the complementary roles of governance and human capital in improving financial transparency and corporate reputation. Firms aiming to boost their reputation should prioritize strategic investments in internal control personnel while strengthening governance frameworks to maximize effectiveness.